Secondary battery and electronic device

By regulating the horizontal stretching intensity and puncture strength of the diaphragm, the problem of cylindrical secondary batteries in the impact test fails, and realizes the impact passage and safety of the secondary battery when the energy density is not reduced. performance.

CN119366050APending Publication Date: 2025-01-24XIAMEN AMPACE TECH LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202380026475.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Cylindrical secondary batteries are prone to axial squirming during vibration and impact tests, resulting in failure. The prior art increases the passing rate by increasing friction, but will lead to a decrease in energy density.

Method used

By regulating the horizontal stretching intensity and puncture strength of the diaphragm, it can make it within the range of 10 mpa to 20 mPa and 0.1 n/μm to 0.8 n/μm, and meet the value of 0.1A+0.2B between 1.02 and 2.16. In order to increase the impact passing rate of the secondary battery.

Benefits of technology

On the basis of taking into account the energy density, the impact pass rate of the secondary battery is improved, and its safety performance and energy density are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119366050A_ABST
    Figure CN119366050A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery and an electronic device, the secondary battery comprises an electrode assembly, the electrode assembly comprises a positive pole piece, a negative pole piece and a diaphragm arranged between the positive pole piece and the negative pole piece; the transverse tensile strength of the diaphragm is A MPa, the puncture strength of the diaphragm is B N / mu m, and A and B meet the following conditions: 1.02 < = 0.1 A + 0.2 B < = 2.16, 10 < = A < = 20, and 0.1 < = B < = 0.8. The secondary battery provided by the invention has good impact passing rate and energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a secondary battery and an electronic device. Background Art

[0002] Cylindrical secondary batteries (such as lithium-ion batteries) have the advantages of standard products, high automation, low cost, good consistency and high energy density, and can be applied to irregular shells in actual use and are widely used. However, cylindrical secondary batteries also have their own problems. For example, cylindrical secondary batteries fail due to axial movement during vibration and impact tests.

[0003] Existing cylindrical secondary batteries often use expansion tape to increase friction to improve the passing rate of cylindrical secondary batteries in impact tests, but this solution will lead to a decrease in the energy density of cylindrical secondary batteries. Therefore, developing a new technical solution to improve the passing rate of impact tests of cylindrical secondary batteries has become a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention

[0004] The purpose of the present application is to provide a secondary battery and an electronic device, so as to improve the impact pass rate of the secondary battery while taking into account the energy density.

[0005] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of secondary batteries to explain this application, but the secondary batteries of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:

[0006] The first aspect of the present application provides a secondary battery, including an electrode assembly, the electrode assembly including a positive electrode sheet, a negative electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet; the transverse tensile strength of the separator is A MPa, the puncture strength of the separator is BN / μm, and A and B satisfy: 1.02≤0.1A+0.2B≤2.16, 10≤A≤20, 0.1≤B≤0.8. The present application regulates the transverse tensile strength and puncture strength of the separator within the above range, and makes the transverse tensile strength and puncture strength of the separator satisfy 1.02≤0.1A+0.2B≤2.16, so that the separator has good strength and toughness when the secondary battery is hit or dropped, so as to buffer the impact force inside the secondary battery, have a good protective effect on the electrode assembly, and reduce the risk of deformation and failure of the electrode assembly, so that the secondary battery can improve its impact pass rate while taking into account the energy density, so that the secondary battery has good safety performance and high energy density.

[0007] In one embodiment of the present application, 1.1≤0.1A+0.2B≤1.6.

[0008] In one embodiment of the present application, 11≤A≤15.

[0009] In one embodiment of the present application, 0.2≤B≤0.6.

[0010] In one embodiment of the present application, the positive electrode sheet includes a positive current collector, the tensile strength of the positive current collector is CMPa, and A and C satisfy: 0.048≤A / C≤0.25. Regulating the value of A / C within the above range is conducive to making the secondary battery have a higher impact pass rate while taking into account the energy density.

[0011] In one embodiment of the present application, 80≤C≤250.

[0012] In one embodiment of the present application, the volume percentage of the separator is 6% to 14% based on the volume of the electrode assembly. By adjusting the volume percentage of the separator within the above range, the impact passing rate of the secondary battery can be improved while taking into account the energy density of the secondary battery, so that the secondary battery has good safety performance and high energy density.

[0013] In one embodiment of the present application, the volume percentage of the separator is 7% to 10% based on the volume of the electrode assembly. By adjusting the volume percentage of the separator within the above range, the impact pass rate of the secondary battery can be further improved while taking into account the energy density of the secondary battery.

[0014] In one embodiment of the present application, the diaphragm includes a base film and an inorganic coating disposed on at least one surface of the base film, the base film includes at least one of polypropylene or polyethylene, the inorganic coating includes inorganic particles and a coating binder, the inorganic particles include at least one of aluminum oxide, boehmite, titanium dioxide, silicon dioxide, zirconium dioxide, tin dioxide, magnesium hydroxide, magnesium oxide, zinc oxide, barium sulfate, boron nitride or aluminum nitride, and the coating binder includes at least one of polyvinylidene fluoride, polyacrylic acid, polymethyl methacrylate, polybutyl acrylate or polyacrylonitrile.

[0015] In one embodiment of the present application, the thickness of the base film is 7 μm to 19 μm, and the total thickness of the inorganic coating is 0.5 μm to 7 μm. By adjusting the thickness of the base film and the inorganic coating within the above range, the diaphragm can have good transverse tensile strength and puncture strength, and can make the secondary battery have good strength and toughness when it is hit or dropped, and can buffer the impact force inside the secondary battery, have a good protective effect on the electrode assembly, and reduce the risk of deformation and failure of the electrode assembly, thereby improving the impact pass rate of the secondary battery while taking into account the energy density of the secondary battery, so that the secondary battery has good safety performance and high energy density.

[0016] In one embodiment of the present application, the thickness of the base film is 9 μm to 15 μm; and / or the total thickness of the inorganic coating is 1 μm to 4 μm. By adjusting the thickness of the base film and / or the inorganic coating within the above range, the transverse tensile strength and puncture strength of the separator can be further improved, thereby facilitating further improving the impact pass rate of the secondary battery while taking into account the energy density of the secondary battery.

[0017] The second aspect of the present application provides an electronic device, wherein the electronic device comprises the secondary battery described in any of the above embodiments. Therefore, the electronic device has good safety performance.

[0018] Beneficial effects of the embodiments of the present application:

[0019] The embodiments of the present application provide a secondary battery and an electronic device. The secondary battery controls the transverse tensile strength and puncture strength of the diaphragm within the above range, and makes the transverse tensile strength and puncture strength of the diaphragm satisfy 1.02≤0.1A+0.2B≤2.16. When the secondary battery is hit or dropped, the diaphragm has good strength and toughness to buffer the impact force inside the secondary battery, has good protection for the electrode assembly, and reduces the risk of deformation and failure of the electrode assembly. Therefore, the impact pass rate of the secondary battery is improved while taking into account the energy density, so that the secondary battery has good safety performance and high energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings described herein are used to provide further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute improper limitations on the present application.

[0021] Figure 1 This is a schematic diagram of the cross-sectional structure of a diaphragm along its thickness direction according to an embodiment of the present application. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical scheme, and advantages of the present application more clearly understood, the present application is further described in detail with reference to the accompanying drawings and examples. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0023] It should be noted that in the specific implementation of the present application, lithium-ion batteries are used as an example of secondary batteries to explain the present application, but the secondary batteries of the present application are not limited to lithium-ion batteries. The specific technical solutions are as follows:

[0024] A first aspect of the present application provides a secondary battery, including an electrode assembly, the electrode assembly including a positive electrode sheet, a negative electrode sheet, and a separator arranged between the positive electrode sheet and the negative electrode sheet; the transverse tensile strength of the separator is A MPa, the puncture strength of the separator is BN / μm, and A and B satisfy: 1.02≤0.1A+0.2B≤2.16, 10≤A≤20, 0.1≤B≤0.8.

[0025] For example, the value of 0.1A+0.2B is 1.02, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.16 or any value between any two of the above numerical ranges. For example, A is 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or any value between any two of the above numerical ranges. For example, B is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or any value between any two of the above numerical ranges. The transverse tensile strength of the diaphragm is less than 10MPa. If the transverse tensile strength of the diaphragm is too low, the diaphragm is prone to breakage when the secondary battery is impacted or dropped, thereby affecting the impact pass rate of the secondary battery. The transverse tensile strength of the diaphragm is greater than 20MPa. If the transverse tensile strength of the diaphragm is too high, the toughness of the diaphragm will deteriorate. The buffering capacity of the diaphragm will deteriorate for the impact force generated by the secondary battery under impact or dropped conditions, and the secondary battery will easily deform and fail, thereby affecting the impact pass rate of the secondary battery. The puncture strength of the diaphragm is less than 0.1N / μm. If the puncture strength of the diaphragm is too low, when the secondary battery generates impact force under conditions such as collision or falling, the strength of the diaphragm is insufficient and the impact force that can be offset is small, which will cause damage to the electrode assembly, contact between the positive electrode plate and the negative electrode plate, and thus cause the secondary battery to fail. If the puncture strength of the diaphragm is greater than 0.8N / μm, the puncture strength of the diaphragm is too high, resulting in poor toughness of the diaphragm and poor buffering capacity of the diaphragm. The secondary battery will easily deform and fail, thereby affecting the impact pass rate of the secondary battery. When the value of 0.1A+0.2B is less than 1.02, the transverse tensile strength and puncture strength of the diaphragm are too low. When the secondary battery is impacted or dropped, the diaphragm is prone to breakage or insufficient strength, which will cause damage to the electrode assembly and contact between the positive and negative pole pieces, leading to failure of the secondary battery. When the value of 0.1A+0.2B is greater than 2.16, the transverse tensile strength and puncture strength of the diaphragm are too high, which will lead to poor toughness of the diaphragm. The buffering capacity of the diaphragm is poor for the impact force generated by the secondary battery under impact or drop conditions, and the secondary battery is prone to deformation and failure, thereby affecting the impact pass rate of the secondary battery. The present application regulates the transverse tensile strength and puncture strength of the diaphragm within the above-mentioned range, and makes the transverse tensile strength and puncture strength of the diaphragm satisfy 1.02≤0.1A+0.2B≤2.16, so that when the secondary battery is hit or dropped, the diaphragm has good strength and toughness without increasing the thickness, so as to buffer the impact force inside the secondary battery, have a good protective effect on the electrode assembly, and reduce the risk of deformation and failure of the electrode assembly, thereby improving the impact pass rate of the secondary battery while taking into account the energy density, and making the secondary battery have good safety performance and high energy density.

[0026] In the present application, the transverse tensile strength is the transverse tensile strength known in the art. The present application has no particular restrictions on the regulation method of the transverse tensile strength of the diaphragm, as long as the purpose of the present application can be achieved. For example, it can be achieved by regulating the thickness of the base film in the diaphragm.

[0027] In the present application, the puncture strength is a puncture strength known in the art. The present application has no particular restrictions on the regulation method of the puncture strength of the diaphragm, as long as the purpose of the present application can be achieved. For example, it can be achieved by regulating the thickness of the inorganic coating in the diaphragm.

[0028] In one embodiment of the present application, 1.1≤0.1A+0.2B≤1.6. For example, the value of 0.1A+0.2B is 1.1, 1.2, 1.3, 1.4, 1.5, 1.6 or any value between any two of the above ranges. By adjusting the value of 0.1A+0.2B within the above range, the overall strength and rigidity of the secondary battery can be adjusted, so that the secondary battery has a better anti-impact effect under conditions such as impact or falling, and the risk of failure caused by the protrusion of the positive active material or the negative active material of the secondary battery due to external force and then piercing the diaphragm is reduced, which is beneficial to further improve the impact pass rate of the secondary battery while taking into account the energy density of the secondary battery.

[0029] In one embodiment of the present application, 11≤A≤15. For example, A is 11, 12, 13, 14, 15 or any value between any two of the above ranges. By regulating the transverse tensile strength of the diaphragm within the above range, the deformation of the diaphragm is small, the probability of fracture is small, and the possibility of brittle fracture of the diaphragm when squeezed is also small, which is conducive to further improving the impact pass rate of the secondary battery while taking into account the energy density of the secondary battery.

[0030] In one embodiment of the present application, 0.2≤B≤0.6. For example, B is 0.2, 0.3, 0.4, 0.5, 0.6 or any value between any two of the above ranges. By regulating the puncture strength of the diaphragm within the above range, the deformation of the diaphragm is small, the probability of fracture is small, and the possibility of brittle fracture of the diaphragm when squeezed is also small, which is conducive to further improving the impact pass rate of the secondary battery on the basis of taking into account the energy density of the secondary battery.

[0031] In one embodiment of the present application, the positive electrode plate includes a positive current collector, the tensile strength of the positive current collector is CMPa, and A and C satisfy: 0.048≤A / C≤0.25. For example, the value of A / C is 0.048, 0.1, 0.15, 0.2, 0.25 or any value between any two of the above numerical ranges. By regulating the value of A / C within the above range, the difference between the transverse tensile strength of the diaphragm and the mechanical properties of the positive current collector is small, the risk of diaphragm fracture is small, and the diaphragm can have a relatively suitable transverse tensile strength. The secondary battery is brittlely fractured during impact deformation under conditions such as impact or falling, or the probability of positive / negative active material particles and positive current collector burrs puncturing the diaphragm to cause secondary battery failure is reduced, which is beneficial to improve its impact pass rate while taking into account the energy density of the secondary battery.

[0032] In one embodiment of the present application, the tensile strength C of the positive electrode current collector is 80 MPa to 250 MPa. For example, the tensile strength of the positive electrode current collector is 80 MPa, 100 MPa, 130 MPa, 160 MPa, 190 MPa, 220 MPa, 250 MPa, or any value between any two of the above ranges. Regulating the tensile strength of the positive electrode current collector within the above range is beneficial to improving the impact pass rate of the secondary battery while taking into account the energy density of the secondary battery.

[0033] The present application has no particular restrictions on the method for regulating the tensile strength of the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it can be achieved by regulating at least one of the grade or state of the positive electrode current collector material, and the grade and state refer to the standard GB / T 3198-2010 "Aluminum and aluminum alloy foil".

[0034] In one embodiment of the present application, the volume percentage of the diaphragm is 6% to 14% based on the volume of the electrode assembly. For example, the volume percentage of the diaphragm is 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or any value between any two of the above numerical ranges. When the volume percentage of the diaphragm is regulated within the above range, the diaphragm has a good protective effect on the electrode assembly, which can make the secondary battery have a suitable impedance and reduce the risk of lithium deposition on the negative electrode during the charging and discharging of the secondary battery, thereby reducing the risk of internal short circuit caused by lithium deposition and causing secondary battery failure. Thus, on the basis of taking into account the energy density of the secondary battery, the impact pass rate of the secondary battery can be improved, so that the secondary battery has good safety performance and a higher energy density.

[0035] In one embodiment of the present application, the volume percentage of the separator is 7% to 10% based on the volume of the electrode assembly. For example, the volume percentage of the separator is 7%, 8%, 9%, 10%, or any value between any two of the above ranges. By adjusting the volume percentage of the separator within the above range, the impact pass rate of the secondary battery can be further improved while taking into account the energy density of the secondary battery.

[0036] The present application has no particular restrictions on the method for regulating the volume percentage of the separator, as long as the purpose of the present application can be achieved. For example, it can be achieved by regulating at least one of the thickness of the separator, the thickness of the positive electrode sheet, or the thickness of the negative electrode sheet.

[0037] In one embodiment of the present application, the diaphragm includes a base film and an inorganic coating disposed on at least one surface of the base film. The above-mentioned "inorganic coating disposed on at least one surface of the base film" means that the inorganic coating can be disposed on both surfaces of the base film, or on one surface of the base film. For ease of understanding, in the present application, the length direction of the diaphragm itself is defined as Y, and the thickness direction of the diaphragm itself is defined as Z. It should be understood that the above definition of direction is for the convenience of describing the purpose of this application, and the direction defined in this application can be understood based on the relative position of the accompanying drawings and the actual product elements. In addition, the length direction and thickness direction of the base film and the inorganic coating themselves are the same as those of the diaphragm. For example, Figure 1 As shown, the diaphragm 10 includes a base film 11 and an inorganic coating 12 disposed on both surfaces of the base film 11. Of course, in some embodiments, the diaphragm includes a base film and an inorganic coating disposed on one surface of the base film. The base film includes at least one of polypropylene or polyethylene, the inorganic coating includes inorganic particles and a coating binder, the inorganic particles include at least one of aluminum oxide, boehmite, titanium dioxide, silicon dioxide, zirconium dioxide, tin dioxide, magnesium hydroxide, magnesium oxide, zinc oxide, barium sulfate, boron nitride or aluminum nitride, and the coating binder includes at least one of polyvinylidene fluoride, polyacrylic acid, polymethyl methacrylate, polybutyl acrylate or polyacrylonitrile. The above-mentioned type of diaphragm has good transverse tensile strength and puncture strength, which can make the secondary battery have good strength and toughness when it is hit or dropped, can buffer the impact force inside the secondary battery, has a good protective effect on the electrode assembly, and reduces the risk of deformation and failure of the electrode assembly, thereby improving the impact pass rate of the secondary battery on the basis of taking into account the energy density of the secondary battery, so that the secondary battery has good safety performance and high energy density.

[0038] In one embodiment of the present application, based on the mass of the inorganic coating, the mass percentage of the inorganic particles is 45% to 55%, and the mass percentage of the coating binder is 45% to 55%.

[0039] In one embodiment of the present application, the Dv50 of the inorganic particles is 0.5 μm to 1.4 μm. In the present application, Dv50 represents the particle size of the inorganic particles in the volume-based particle size distribution, starting from the small particle size side, reaching a volume accumulation of 50%. The present application does not particularly limit the test method of the Dv50 of the inorganic particles, as long as the purpose of the present application can be achieved. For example, the Dv50 can be measured using a laser particle size analyzer (such as MalvernMaster Size 3000) with reference to the national standard GB / T 19077-2016 ("Laser Diffraction Method for Particle Size Distribution").

[0040] In one embodiment of the present application, the thickness of the base film is 7 μm to 19 μm, and the total thickness of the inorganic coating is 0.5 μm to 7 μm. For example, the thickness of the base film is 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 17 μm, 19 μm or any value between any two of the above numerical ranges. For example, the total thickness of the inorganic coating is 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or any value between any two of the above numerical ranges. It should be noted that the above-mentioned "total thickness of the inorganic coating" refers to the sum of the thicknesses of the inorganic coatings in the diaphragm. Exemplarily, in some embodiments, the inorganic coating is disposed on one surface of the base film, and the diaphragm contains a single layer of inorganic coating, then the total thickness of the inorganic coating is the thickness of the single layer of inorganic coating; in other embodiments, the inorganic coating is disposed on both surfaces of the base film, and the diaphragm contains a double layer of inorganic coating, then the total thickness of the inorganic coating is the thickness of the double layer of inorganic coating. By adjusting the thickness of the base film and the inorganic coating within the above range, the diaphragm can have good transverse tensile strength and puncture strength, and can make the secondary battery have good strength and toughness when it is hit or dropped, and can buffer the impact force inside the secondary battery, have a good protective effect on the electrode assembly, and reduce the risk of deformation and failure of the electrode assembly, thereby improving the impact pass rate of the secondary battery and making the secondary battery have good safety performance.

[0041] In one embodiment of the present application, the thickness of the base film is 9 μm to 15 μm. For example, the thickness of the base film is 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or any value between any two of the above ranges. By adjusting the thickness of the base film within the above range, the transverse tensile strength of the diaphragm can be further improved, and the diaphragm has a suitable thickness, which can reduce the probability of damage to the energy density of the secondary battery due to the increase in the thickness of the diaphragm, thereby facilitating the further improvement of the impact pass rate of the secondary battery while taking into account the energy density of the secondary battery.

[0042] In one embodiment of the present application, the total thickness of the inorganic coating is 1 μm to 4 μm. For example, the total thickness of the inorganic coating is 1 μm, 2 μm, 3 μm, 4 μm, or any value between any two of the above numerical ranges. By regulating the thickness of the inorganic coating within the above range, the puncture strength of the diaphragm can be further improved, and the diaphragm has a suitable thickness, which can reduce the probability of damage to the energy density of the secondary battery due to the increase in the thickness of the diaphragm, thereby facilitating the further improvement of the impact pass rate of the secondary battery while taking into account the energy density of the secondary battery.

[0043] In one embodiment of the present application, the thickness of the base film is 9 μm to 15 μm, and the total thickness of the inorganic coating is 1 μm to 4 μm. For example, the thickness of the base film is 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or any value between any two of the above numerical ranges. The total thickness of the inorganic coating is 1 μm, 2 μm, 3 μm, 4 μm or any value between any two of the above numerical ranges. Regulating the thickness of the base film and the inorganic coating within the above range can further improve the transverse tensile strength and puncture strength of the diaphragm, and making the diaphragm have a suitable thickness can reduce the probability of damage to the energy density of the secondary battery due to the increase in the thickness of the diaphragm, which is beneficial to further improve the impact pass rate of the secondary battery while taking into account the energy density of the secondary battery.

[0044] The present application has no particular restrictions on the positive electrode plate, as long as the purpose of the present application can be achieved. For example, the positive electrode plate includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector. In some embodiments, the positive active material layer is disposed on one surface of the positive current collector. In other embodiments, the positive active material layer is disposed on both surfaces of the positive current collector, wherein the above-mentioned "surface" may be a partial surface or the entire surface of the positive current collector. The present application has no particular restrictions on the type of positive current collector, as long as the purpose of the present application can be achieved. For example, the positive current collector may include aluminum foil, aluminum alloy foil, etc. The positive active material layer of the present application includes positive active materials. The present application has no particular restrictions on the type of positive active materials, as long as the transition metal elements of the present application are included and the purpose of the present application can be achieved. For example, the positive active material may include lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O 2 ), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO 2) at least one of lithium manganate, lithium iron manganese phosphate, lithium titanate, etc. In the present application, the positive electrode active material may further contain non-metal elements. For example, the non-metal elements include at least one of fluorine, phosphorus, boron, chlorine, silicon or sulfur, and these elements can further improve the stability of the positive electrode active material. In the present application, there is no particular limitation on the thickness of the positive electrode current collector and the positive electrode active material layer, as long as the object of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, and further, the thickness of the positive electrode current collector can be 6 μm to 18 μm. The thickness of the positive electrode active material layer is 30 μm to 120 μm.

[0045] Optionally, the positive electrode active material layer may further include a positive electrode conductive agent and a positive electrode binder. The present application has no particular limitation on the types of the positive electrode conductive agent and the positive electrode binder in the positive electrode active material layer, as long as the object of the present application can be achieved. The present application has no particular limitation on the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder in the positive electrode active material layer. Those skilled in the art can select according to actual needs as long as the object of the present application can be achieved. For example, the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder in the positive electrode active material layer is (95-98):(0.5-2.5):(1.5-3.4).

[0046] The present application has no particular limitation on the negative electrode sheet, as long as the object of the present application can be achieved. For example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer provided on at least one surface of the negative electrode current collector. In some embodiments, the negative electrode active material layer is provided on one surface of the negative electrode current collector. In other embodiments, the negative electrode active material layer is provided on two surfaces of the negative electrode current collector. Among them, the above "surface" can be a partial surface or the entire surface of the negative electrode current collector. The negative electrode active material layer of the present application contains a negative electrode active material. The present application has no particular limitation on the type of the negative electrode active material, as long as the object of the present application can be achieved. For example, the negative electrode active material may contain natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO x (0 < x < 2), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO 2 , Li-Al alloy or metallic lithium, etc. at least one of them. In the present application, there is no particular limitation on the thickness of the negative electrode current collector and the negative electrode active material layer, as long as the object of the present application can be achieved. For example, the thickness of the negative electrode current collector is 6 μm to 10 μm, and the thickness of the negative electrode active material layer is 30 μm to 130 μm.

[0047] Optionally, the negative electrode active material layer may also include at least one of a negative electrode conductor, a thickener, and a negative electrode binder. The present application does not particularly limit the types of negative electrode conductors, thickeners, and negative electrode binders in the negative electrode active material layer, as long as the purpose of the present application can be achieved. The present application does not particularly limit the mass ratio of the negative electrode active material, the negative electrode conductor, the thickener, and the negative electrode binder in the negative electrode active material layer, as long as the purpose of the present application can be achieved. For example, the mass ratio of the negative electrode active material, the negative electrode conductor, the thickener, and the negative electrode binder in the negative electrode active material layer is (96-98): (0.5-2): (0-1.5): (1.0-1.9).

[0048] In one embodiment of the present application, the secondary battery further includes an electrolyte and a shell. The present application has no particular limitation on the electrolyte and the shell, and they may be electrolytes and shells known in the art, as long as the purpose of the present application can be achieved.

[0049] The present application does not particularly limit the type of secondary battery, which may include any device that undergoes an electrochemical reaction. For example, the secondary battery may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a sodium ion secondary battery (sodium ion battery), a lithium polymer secondary battery, and a lithium ion polymer secondary battery.

[0050] The present application has no particular limitation on the preparation method of the diaphragm, and any preparation method known in the art may be selected as long as the purpose of the present application can be achieved.

[0051] For example, in one embodiment, the preparation method of the diaphragm includes but is not limited to the following steps: (1) uniformly mixing inorganic particles and a coating binder to obtain an inorganic coating slurry having a solid content of 50 wt% to 55 wt%; (2) coating the inorganic coating slurry on one surface of the base film, and drying to form an inorganic coating, thereby obtaining the diaphragm. The present application does not particularly limit the drying temperature and time in the above step (2), and those skilled in the art can select and adjust according to actual needs, as long as the purpose of the present application can be achieved.

[0052] For example, in another embodiment, the preparation method of the diaphragm includes but is not limited to the following steps: (1) uniformly mixing inorganic particles and coating binder to obtain inorganic coating slurry with a solid content of 50wt% to 55wt%; (2) coating the inorganic coating slurry on one surface of the base film, and forming a single-layer inorganic coating after drying; (3) coating the inorganic coating slurry on the other surface of the base film, and forming a double-layer inorganic coating after drying, so as to obtain the diaphragm. The present application does not particularly limit the drying temperature and time in the above steps (2) and (3), and those skilled in the art can select and adjust according to actual needs, as long as the purpose of the present application can be achieved.

[0053] The present application does not particularly limit the preparation method of the secondary battery, and the preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the secondary battery includes but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery; or, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery.

[0054] The second aspect of the present application provides an electronic device, wherein the electronic device comprises the secondary battery described in any of the above embodiments. Therefore, the electronic device has good safety performance.

[0055] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. For example, the electronic device can include, but is not limited to: a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.

[0056] Example

[0057] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods.

[0058] Test methods and equipment:

[0059] Test of transverse tensile strength A of diaphragm:

[0060] The lithium-ion battery was disassembled to obtain the diaphragm, which was then immersed in a dimethyl carbonate (DMC) solution for 2 hours and dried, and then tested according to the national standard "GB / T 36363-2018 Polyolefin diaphragm for lithium-ion batteries".

[0061] During the test, the width direction along the expanded state of the diaphragm is defined as the transverse direction.

[0062] Test of puncture strength B of diaphragm:

[0063] The lithium-ion battery was disassembled to obtain the diaphragm, which was soaked in a DMC solution for 2 hours and then dried, and then tested according to the national standard "GB / T 36363-2018 Polyolefin diaphragm for lithium-ion batteries".

[0064] Test of tensile strength C of positive electrode current collector:

[0065] ① Disassemble the lithium-ion battery to obtain the positive electrode sheet, use N-methylpyrrolidone (NMP) to scrub away the positive electrode active material layer, and obtain the positive electrode current collector;

[0066] ② Test according to "YB / T 4334-2013 Metal Foil Room Temperature Tensile Test Method" and "GB / T 228-2010 Metal Material Tensile Test Part 1: Room Temperature Test Method".

[0067] Measurement and calculation of diaphragm volume percentage:

[0068] The fully charged lithium-ion battery was disassembled to obtain the positive electrode sheet, negative electrode sheet and separator. The positive electrode sheet, negative electrode sheet and separator were respectively placed in a newly opened DMC solution for cleaning, and after drying, the following measurements and calculations were performed:

[0069] (1) Calculation of diaphragm volume: Measure the width W of the diaphragm using an optical microscope. 1 , Use a tape measure to measure the length of the diaphragm L 1 , Micrometer to measure the thickness of the diaphragm T 1 , the volume of the diaphragm V 1 =W 1 ×L 1 ×T 1 ;

[0070] (2) Calculation of the volume of the electrode assembly: Use an optical microscope to measure the width W of the positive electrode sheet. 2 and the width W of the negative electrode 3 , use a soft ruler to measure the length L of the positive electrode 2 and the length L of the negative electrode 3 , and micrometers to measure the thickness T of the positive electrode sheet 2 and the thickness of the negative electrode sheet T 3 ;

[0071] The volume of the positive electrode V 2 =W 2 ×L 2 ×T 2 , the volume of the negative electrode V 3 =W 3 ×L 3 ×T 3 ;

[0072] Volume of the electrode assembly V4 =V 1 +V 2 +V 3 ;

[0073] (3) Volume percentage of the diaphragm (%) = V 1 / V 4 ×100%.

[0074] Impact pass rate test:

[0075] After charging the lithium-ion batteries of the embodiments and comparative examples to 4.2V at a constant current of 2C, charge them to 0.05C at a constant voltage of 4.2V to reach a fully charged state. Place the fully charged lithium-ion battery on a test bench, and place a round bar with a diameter of φ15.8mm and a length of 15.8cm at the center of the wide surface of the lithium-ion battery. The longitudinal axis of the lithium-ion battery and the longitudinal axis of the round bar are parallel to the surface of the test bench, and the longitudinal axis of the lithium-ion battery is perpendicular to the longitudinal axis of the round bar (in a cross shape). Use a 9.1kg heavy hammer to drop vertically from a height of 610mm in a free state and fall at the intersection of the round bar and the lithium-ion battery. The above lithium-ion battery is a cylindrical lithium-ion battery.

[0076] Judgment criteria: Passed if there is no fire, explosion or leakage.

[0077] Twenty lithium-ion batteries were tested for each embodiment or comparative example, and the impact passing rate = the number of passed batteries / 20.

[0078] Energy density test:

[0079] First, the lithium-ion battery is charged according to the following operating process, and then discharged to obtain the discharge capacity of the lithium-ion battery.

[0080] Charging: Charge at 2C constant current to 4.2V, then charge at 4.2V constant voltage to 0.05C;

[0081] Discharge: Discharge at 0.2C constant current to 2.5V, and obtain the discharge energy E1;

[0082] After the lithium-ion battery charging step is completed, the length L, width W, and height H of the lithium-ion battery are tested with a laser thickness gauge to obtain the volume V = L × W × H of the lithium-ion battery. Its volume energy density (ED) can be calculated by the following formula: ED (Wh / L) = E1 / V.

[0083] Example 1

[0084] <Preparation of Separator>

[0085] A polyethylene film with a thickness of 7 μm was used as the base film;

[0086] The inorganic particles of boehmite and the coating binder polyvinylidene fluoride are mixed in a mass ratio of 1:1, deionized water is added as a solvent, and the mixture is stirred evenly to form an inorganic coating slurry with a solid content of 50 wt%; the Dv50 of the inorganic particles is 0.7 μm;

[0087] The inorganic coating slurry is coated on one surface of the base film and dried at 90°C to form a single-layer inorganic coating. Then, the inorganic coating slurry is coated on the other surface of the base film and dried at 100°C to form a double-layer inorganic coating, thus obtaining a separator. The thickness of the single-layer inorganic coating is 1 μm, and the total thickness of the inorganic coating is 2 μm.

[0088] <Preparation of positive electrode sheet>

[0089] The positive electrode active material is lithium nickel cobalt manganese oxide (Ni91, LiNi 0.91 Co 0.04 Mn 0.05 O 2 ), positive electrode binder polyvinylidene fluoride (PVDF, weight average molecular weight is 70×10 5 ), the positive electrode conductive agent and conductive carbon black are mixed in a mass ratio of 94.8:2.8:2.4, N-methylpyrrolidone (NMP) is added as a solvent, and stirred under the action of a vacuum mixer to a positive electrode slurry with a solid content of 75wt% and a uniform system. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 13μm, and dried at 90°C to obtain a positive electrode sheet coated with a single-sided positive electrode active material layer. After that, the above steps are repeated on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a double-sided positive electrode active material layer. After cold pressing, cutting, and welding of aluminum pole ears, a positive electrode sheet with a specification of 60mm×1580mm is obtained for standby use. Among them, the compaction density of the positive electrode active material layer is 2.69g / cm 3 The single layer thickness of the positive electrode active material layer is 38.5 μm, and the thickness of the positive electrode sheet is 90 μm.

[0090] Aluminum foil brand: 5052, state: O, reference standard: GB / T 3198-2010 "Aluminum and aluminum alloy foil".

[0091] <Preparation of negative electrode sheet>

[0092] The negative electrode active material artificial graphite and thickener carboxymethyl cellulose (CMC, weight average molecular weight 7×10 5 ), negative electrode binder styrene butadiene rubber (SBR, weight average molecular weight 50×10 5) are mixed in a mass ratio of 97:1.7:1.3, and then deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the solid content is 51wt% and the system is uniform. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10μm, and dried at 90°C to obtain a negative electrode sheet coated with a negative electrode active material layer on one side. Thereafter, the above steps are repeated on the other surface of the copper foil to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides. After cold pressing, cutting, and welding of copper ears, a negative electrode sheet with a specification of 62mm×1600mm is obtained for standby use. Among them, the compaction density of the negative electrode active material layer is 1.6g / cm 3 The single layer thickness of the negative electrode active material layer is 58.5 μm, and the thickness of the negative electrode sheet is 127 μm.

[0093] <Preparation of Electrolyte>

[0094] In an environment with a water content of less than 10 ppm, non-aqueous organic solvents of ethylene carbonate (EC), diethyl carbonate (DEC), and propylene carbonate (PC) were mixed in a mass ratio of 30:40:30, and then lithium hexafluorophosphate (LiPF6) was added to the non-aqueous organic solvent. 6 ) are dissolved and mixed evenly to obtain an electrolyte, wherein LiPF 6 The concentration is 1 mol / L.

[0095] <Preparation of lithium-ion batteries>

[0096] The positive electrode sheet, separator, negative electrode sheet and separator are stacked in order and wound to obtain an electrode assembly. The electrode assembly is placed in a cylindrical shell, and after drying, the electrolyte is injected. After vacuum packaging, standing, formation, capacity, degassing, trimming and other processes, a cylindrical lithium-ion battery is obtained. Among them, the material of the cylindrical shell is steel shell.

[0097] Example 2 to Example 14

[0098] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1.

[0099] Among them, when the thickness of the base film or the total thickness of the inorganic coating changes, the thickness of the negative electrode plate changes accordingly, so that the volume percentage of the separator is as shown in Table 1. When the thickness of the negative electrode plate changes, the thickness of the negative electrode collector remains unchanged, and the single layer thickness of the negative electrode active material layer changes.

[0100] Example 15 to Example 19

[0101] Except for adjusting the volume percentage of the diaphragm according to Table 1, the rest is the same as Example 3.

[0102] Among them, the volume percentage of the separator is changed by adjusting the thickness of the negative electrode plate. When the thickness of the negative electrode plate changes, the thickness of the negative electrode collector remains unchanged, and the single layer thickness of the negative electrode active material layer changes.

[0103] Embodiment 20

[0104] The process is the same as Example 3 except that the grade of aluminum foil in <Preparation of Positive Electrode Sheet> is adjusted to 2A11 and the state is adjusted to H18 so that the tensile strength of the positive electrode current collector is as shown in Table 1.

[0105] Embodiment 21

[0106] The process is the same as that of Example 3 except that the grade of the aluminum foil in <Preparation of Positive Electrode Sheet> is adjusted to 3003 so that the tensile strength of the positive electrode current collector is as shown in Table 1.

[0107] Embodiment 22

[0108] The process is the same as that of Example 3 except that the grade of the aluminum foil in <Preparation of Positive Electrode Sheet> is adjusted to 8006 so that the tensile strength of the positive electrode current collector is as shown in Table 1.

[0109] Embodiment 23

[0110] Except that the grade of aluminum foil in <Preparation of positive electrode sheet> is adjusted to 3003 and the state is adjusted to H18 so that the tensile strength of the positive electrode current collector is as shown in Table 1, the rest is the same as Example 3.

[0111] Embodiment 24

[0112] The process is the same as Example 3 except that the grade of the aluminum foil in <Preparation of Positive Electrode Sheet> is adjusted to 1060 so that the tensile strength of the positive electrode current collector is as shown in Table 1.

[0113] Comparative Examples 1 to 6

[0114] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1.

[0115] Among them, when the thickness of the base film or the total thickness of the inorganic coating changes, the thickness of the negative electrode plate changes accordingly, so that the volume percentage of the separator is as shown in Table 1. When the thickness of the negative electrode plate changes, the thickness of the negative electrode collector remains unchanged, and the single layer thickness of the negative electrode active material layer changes.

[0116] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Table 1.

[0117] Table 1

[0118]

[0119] From Examples 1 to 19 and Comparative Examples 1 to 6, it can be seen that the secondary battery of the embodiment of the present application can have a higher impact pass rate and a higher energy density by regulating the transverse tensile strength A of the diaphragm and the puncture strength B of the diaphragm within the scope of the present application, and making the transverse tensile strength A and the puncture strength B of the diaphragm satisfy 1.02≤0.1A+0.2B≤2.16, indicating that the secondary battery of the present application can improve its impact pass rate on the basis of taking into account the energy density. However, in the secondary battery of the comparative example, at least one of the transverse tensile strength A of the diaphragm, the puncture strength B of the diaphragm, or the value of 0.1A+0.2B is not within the scope of the present application, and it has a lower impact pass rate, and fails to improve the impact pass rate of the secondary battery on the basis of taking into account the energy density of the secondary battery.

[0120] The transverse tensile strength A of the diaphragm usually affects the impact pass rate and energy density of the secondary battery. It can be seen from Examples 1 to 6, Comparative Examples 1 and 2 that the secondary battery using a diaphragm with a transverse tensile strength A within the range of the present application has a higher impact pass rate and energy density.

[0121] The puncture strength B of the diaphragm usually affects the impact pass rate and energy density of the secondary battery. It can be seen from Examples 3, 7 to 11, Comparative Examples 3 and 4 that the secondary battery using a diaphragm with a puncture strength B within the range of the present application has a higher impact pass rate and energy density.

[0122] The value of 0.1A+0.2B usually affects the impact pass rate and energy density of the secondary battery. It can be seen from Examples 1 to 14, Comparative Examples 1, 2, 5 and 6 that the secondary battery with a value of 0.1A+0.2B within the scope of the present application has a higher impact pass rate and energy density.

[0123] The volume percentage of the diaphragm usually affects the impact pass rate and energy density of the secondary battery. It can be seen from Examples 3 and 15 to 19 that the secondary battery using a diaphragm with a volume percentage within the range of the present application has a higher impact pass rate and energy density.

[0124] The A / C value usually affects the impact pass rate and energy density of the secondary battery. It can be seen from Examples 3 and 20 to 24 that the secondary battery with an A / C value within the range of the present application has a higher impact pass rate and energy density.

[0125] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0126] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0127] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A secondary battery, comprising an electrode assembly, wherein the electrode assembly comprises a positive electrode sheet, a negative electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet; The transverse tensile strength of the diaphragm is A MPa, the puncture strength of the diaphragm is BN / μm, and A and B satisfy: 1.02≤0.1A+0.2B≤2.16, 10≤A≤20, 0.1≤B≤0.

8.

2. The secondary battery according to claim 1, wherein 1.1≤0.1A+0.2B≤1.

6.

3. The secondary battery according to claim 1, wherein 11≤A≤15。 4. The secondary battery according to claim 1, wherein 0.2≤B≤0.6。 5. The secondary battery according to claim 1, wherein The positive electrode sheet includes a positive electrode current collector, the tensile strength of the positive electrode current collector is C MPa, and A and C satisfy: 0.048≤A / C≤0.

25.

6. The secondary battery according to claim 5, wherein 80≤C≤250。 7. The secondary battery according to claim 1, wherein Based on the volume of the electrode assembly, the volume percentage of the separator is 6% to 14%.

8. The secondary battery according to claim 1, wherein Based on the volume of the electrode assembly, the volume percentage of the separator is 7% to 10%.

9. The secondary battery according to claim 1, wherein The diaphragm includes a base film and an inorganic coating disposed on at least one surface of the base film; The base film comprises at least one of polypropylene or polyethylene; The inorganic coating includes inorganic particles and a coating binder, the inorganic particles include at least one of aluminum oxide, boehmite, titanium dioxide, silicon dioxide, zirconium dioxide, tin dioxide, magnesium hydroxide, magnesium oxide, zinc oxide, barium sulfate, boron nitride or aluminum nitride, and the coating binder includes at least one of polyvinylidene fluoride, polyacrylic acid, polymethyl methacrylate, polybutyl acrylate or polyacrylonitrile.

10. The secondary battery according to claim 9, wherein The base film has a thickness of 7 μm to 19 μm, and the inorganic coating has a total thickness of 0.5 μm to 7 μm.

11. The secondary battery according to claim 10, wherein The thickness of the base film is 9 μm to 15 μm; and / or, The total thickness of the inorganic coating layer is 1 μm to 4 μm.

12. An electronic device, wherein: The electronic device includes the secondary battery according to any one of claims 1 to 11.

Citation Information

Cited By

  • Battery monomer, battery device, power utilization device and energy storage device

    CN119833779A

  • Battery cell, battery device, power consumption device, and energy storage device

    CN119833779B